Pengaruh Suhu Penyimpanan terhadap Kadar Parasetamol Sirup Selama Beyond Use Date Secara Spektrofotometri UV-Vis: Effect of Storage Temperature on Paracetamol Syrup Concentration During Beyond Use Date by UV-Vis Spectrophotometry - Indra Meilina Yusefa; Nuraini Harmastuti; Reslely Harjanti (Universitas Ngudi Waluyo, 2024)
Paracetamol or acetaminophen is a widely used analgesic-antipyretic drug worldwide. Paracetamol in liquid form is preferred because of its easy administration and rapid absorption in the body and large doses are easily adjusted for children. Storage of paracetamol syrup in accordance with the etiquette is at controlled room temperature. Beyond use date (BUD) is the time limit for the use of a drug after it has been formulated, prepared or after its primary packaging has been opened or tampered with. The purpose of this study was to determine the effect of storage temperature on paracetamol syrup levels during BUD. Paracetamol syrup was stored in a room with air conditioning (20-25oC) and without air conditioning (30-40oC) for 14 days. Observation of levels was carried out on days 0, 3, 7, 10 and 14 using UV-Vis spectrophotometry with a wavelength of 247 nm and operating time for 22 minutes. The results of the determination of paracetamol syrup levels after storage for 14 days in a room with air conditioning in generic and trademark samples were 90.05 ± 1.34% and 92.73 ± 1.01%, respectively. Paracetamol syrup levels in a room without air conditioning in generic and trademark samples are 79.07 ± 0.99% and 81.10 ± 2.02%. Storage temperature affects paracetamol syrup levels during storage with a difference in levels of 10.98% for generic samples and 11.63% for trademark samples during BUD. ABSTRAK Parasetamol merupakan obat analgesik-antipiretik yang banyak digunakan di seluruh dunia. Parasetamol dalam bentuk cairan lebih disukai karena pemberiannya yang mudah dan cepat terabsorpsi dalam tubuh serta dalam pemberian dosis besar mudah disesuaikan untuk anak. Penyimpanan parasetamol sirup yang sesuai dengan etiket adalah pada suhu ruang terkendali. Beyond use date (BUD) adalah batas waktu penggunaan obat setelah diracik, disiapkan atau setelah kemasan primernya dibuka atau dirusak. Tujuan penelitian ini adalah untuk mengetahui pengaruh suhu penyimpanan terhadap kadar parasetamol sirup selama BUD. Parasetamol sirup disimpan pada ruang dengan penyejuk udara (20 – 25oC) dan tanpa penyejuk udara (30 – 40oC) selama 14 hari. Pengamatan kadar dilakukan pada hari ke-0, 3, 7, 10 dan 14 menggunakan spektrofotometri UV-Vis dengan panjang gelombang 247 nm dan waktu operasi selama 22 menit. Hasil penetapan kadar parasetamol sirup setelah penyimpanan selama 14 hari di ruang dengan penyejuk udara pada merek generik dan merek dagang berturut-turut yaitu 90,05 ± 1,34% dan 92,73 ± 1,01%. Kadar parasetamol sirup diruang tanpa penyejuk udara pada merek generik dan merek dagang yaitu 79,07 ± 0,99% dan 81,10 ± 2,02%. Suhu penyimpanan mempengaruhi kadar parasetamol sirup selama penyimpanan dengan selisih kadar 10,98% untuk merek generik dan 11,63% untuk merek dagang selama BUD.